Mild cognitive impairment, psychiatric symptoms, and executive functioning in patients with Parkinson's disease. (23rd January 2020) - Petkus, Andrew J.; Filoteo, J. Vincent; Schiehser, Dawn M.; Gomez, Megan E.; Hui, Jennifer S.; Jarrahi, Behnaz; McEwen, Sarah; Jakowec, Michael W.; Petzinger, Giselle M.
Abstract : Objective: Mild cognitive impairment (MCI) and psychiatric symptoms (anxiety, depression, and apathy) are common in Parkinson's disease (PD). While studies have supported the association between psychiatric symptoms and cognitive performance in PD, it is unclear if the magnitude of link between psychiatric symptoms and cognitive health is stronger by MCI status. The purpose of this study was to examine the association between cognitive performance and psychiatric symptoms in PD and whether MCI status moderates this association. Methods/Design: Participants ( N = 187) completed a comprehensive neuropsychological assessment that included measures of attention, language, executive function (EF), visuospatial ability, episodic memory, and psychiatric symptoms. Participants were classified as PD‐MCI ( N = 73) or PD‐normal cognition (NC; N = 114). Linear regression analyses were conducted to examine the association between psychiatric symptoms and cognitive performance and the moderating effect of PD‐MCI status. Results: There were no differences in mean psychiatric symptoms between PD‐MCI and PD‐NC. Psychiatric symptoms were predominantly associated with worse EF. The magnitude of the association between anxiety and worse EF was larger in participants with PD‐MCI compared with PD‐NC. A multivariable regression analysis examining the independent contributions of each symptom demonstrated the most robust association between EF and anxiety. Conclusions: Symptoms of anxiety, depression, and apathy are associated with worse executive functioning in individuals with PD. PD‐MCI may be important in moderating the association between cognitive performance, specifically anxiety, and EF. Factors that promote cognitive resilience may serve as key therapeutic modalities in managing neuropsychiatric symptoms in PD.